Helicobacter pylorienter and survive within multivesicular vacuoles of epithelial cells - Manuel R. Amieva; Nina R. Salama; Lucy S. Tompkins; Stanley Falkow (2002)
Although intracellular Helicobacter pylori have been described in biopsy specimens and in cultured epithelial cells, the fate of these bacteria is unknown. Using differential interference contrast (DIC) video and immunofluorescence microscopy, we document that a proportion of cell-associated H. pylori enter large cytoplasmic vacuoles, where they remain viable and motile and can survive lethal concentrations of extracellular gentamicin. Entry into vacuoles occurs in multiple epithelial cell lines including AGS gastric adenocarcinoma, Caco-2 colon adenocarcinoma and MDCK kidney cell line, and depends on the actin cytoskeleton. Time-lapse microscopy over several hours was used to follow the movement of live H. pylori within vacuoles of a single cell. Pulsed, extracellular gentamicin treatments show that the half-life of intravacuolar bacteria is on the order of 24 h. Viable H. pylori repopulate the extracellular environment in parallel with the disappearance of intravacuolar bacteria, suggesting release from the intravacuolar niche. Using electron microscopy and live fluorescent staining with endosomal dyes, we observe that H. pylori-containing vacuoles are similar in morphology to late endosomal multivesicular bodies. VacA is not required for these events, as isogenic vacA– mutants still enter and survive within the intravacuolar niche. The exploitation of an intravacuolar niche is a new aspect of the biological life cycle of H. pylori that could explain the difficulties in eradicating this infection.